2002
DOI: 10.1128/iai.70.12.6621-6627.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mannoprotein fromCryptococcus neoformansPromotes T-Helper Type 1 Anticandidal Responses in Mice

Abstract: We previously demonstrated that mannoprotein (MP) from Cryptococcus neoformans (CnMP) stimulates interleukin-12 production by human monocytes, thus fostering a T-helper type 1 (Th1) protective anticryptococcal response. In this paper we show that CnMP was also able to induce a Candida albicans-directed protective Th1 response. This was demonstrated for mice immunized with CnMP by induction of a delayed-type hypersensitivity (DTH) reaction to C. albicans MP (CaMP) as well as induction of gamma interferon produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…DCs are able to secrete TNF-␣ and IL-12 when stimulated with MP1 and MP2; this activation involves IB␣ phosphorylation and degradation. IL-12 induction, but not TNF-␣ In a previous paper, we demonstrated that MPs from C. neoformans are able to induce a Th1-type response in vitro by using monocytes and T cells separated from peripheral blood mononuclear cells from healthy donors (36), and in subsequent papers, we demonstrated that immunization with MPs induced protective responses to C. neoformans and C. albicans challenge (33,35). DCs are critical in controlling early innate responses: they regulate long-lasting adaptive immunity and contribute to the maintenance of self-tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DCs are able to secrete TNF-␣ and IL-12 when stimulated with MP1 and MP2; this activation involves IB␣ phosphorylation and degradation. IL-12 induction, but not TNF-␣ In a previous paper, we demonstrated that MPs from C. neoformans are able to induce a Th1-type response in vitro by using monocytes and T cells separated from peripheral blood mononuclear cells from healthy donors (36), and in subsequent papers, we demonstrated that immunization with MPs induced protective responses to C. neoformans and C. albicans challenge (33,35). DCs are critical in controlling early innate responses: they regulate long-lasting adaptive immunity and contribute to the maintenance of self-tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses strong immunogenic properties, including induction of a T-cell response and partial protection against lethal infection (28). Recently we showed that CnMP induces cross-protection against systemic C. albicans challenge and that it is, at least in part, related to epitopes also common to CaMP (35). The protective T-cell response is governed by antigen-presenting cells, and dendritic cells (DCs) are the quintessential professional antigen-presenting cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of a defined peptide epitope activating T H 1 cells with cross-reactivity to the 2 most important fungal pathogens in humans is to our knowledge a novel finding and only little is known in mouse models. 37 The concept of heterologous immunity to different pathogens mediated by cross-reactive T cells has until now only been described in detail for viral infections, 38 for example, for influenza virus 39,40 and flavivirus. 41,42 The discovery of this mechanism has initiated the development of new vaccines that will target conserved protein domains of different flaviviral strains for induction of cross-protection.…”
Section: Discussionmentioning
confidence: 99%
“…These mannoproteins have been the focus of immunologic studies, as they appear to be involved in the induction of cell-mediated immunity (18,28,70,75,82) and cytokine production (48,81), both critical functions for clearing the fungus. Several of these proteins have been purified from acapsular strains of Cryptococcus by concanavalin A affinity (49,66), and one study suggests that they move through the cell wall and are released into the external environment (99).…”
Section: Fig 2 Structures Of the Cryptococcal Capsule Components (A)mentioning
confidence: 99%